Successful treatment of gallbladder mixed adenoneuroendocrine carcinoma with neo-adjuvant chemotherapy - Song Wu; Chen Wenfang; Zhang Sheng; Peng Jianjun; He Yulong (BMC, 2012)
Abstract Mixed adenoneuroendocrine carcinoma (MANEC) carcinomas rarely occur in the gallbladder. Here we reported a case of giant gallbladder unresectable mass with local liver invasion and omentum metastasis, which proved to be neuroendocrine carcinoma (NEC) by biopsy, received successful radical operation after neo-adjuvant chemotherapy plus somatostatin treatment. The patient showed good response as the neoplasm diminished dramatically and showed clear margin after 6 courses of treatment. A radical operation including cholecystectomy, hepatic wedge resection of the gallbladder fossa segment and lymph node of group 8a and 8p resection was performed successfully. Postoperative histopathological examination revealed neuroendocrine carcinoma mixed with adenocarcinoma in the gallbladder wall. Followed up showed no evidence of recurrence after 7 months of the operation. We suggest that neo-adjuvant chemotherapy may be beneficial to gallbladder mixed neuroendocrine carcinomas in an advanced stage which could also be advantageous to NEC of other organs. Virtual slides http://www.diagnosticpathology.diagnomx.eu/vs/2731892837743787